Profitability of Bank Muamalat Indonesia - Delli Maria; Renata Mayang Sari (Prosiding International conference on Information Technology and Business (ICITB), 2021)
Bank Muamalat Indonesia has the first islamic bank in Indonesia which has decreased very drastically in profit. This research aims to proved empirically the factors that affect the profitability of Bank Muamalat Indonesia. The method of analysis used multiple linear regression analysis with the help of SPPS software version 20. The level ofconfidence was 95%. The research data was taken from the Income Statement and Balance Sheet of Bank Muamalat Indonesia. The results of the research have show that the Capital Adequacy Ratio (CAR) and Operating Costs to Operating Income (BOPO) have a significant effect on the profitability (ROA) of Bank Muamalat Indonesia. Meanwhile, Non- Performing Financial (NPF) and Financing to Deposit Ratio (FDR) have no significant effect on Bank Muamalat Indonesia's ability to earn profit.Keywords—Profitability, Bank Muamalat